Vascular Cambium: The Source of Wood Formation - Wang, Dian; Chen, Yan; Li, Wei; Li, Quanzi; Lu, Mengzhu; Zhou, Gongke; Chai, Guohua (Frontiers in Plant Science, 2021)
Wood is the most abundant biomass produced by land plants and is mainly used for timber, pulping, and paper making. Wood (secondary xylem) is derived from vascular cambium and its formation encompasses a series of developmental processes. Extensive studies in Arabidopsis and trees demonstrate that the initiation of vascular stem cells and the proliferation and differentiation of the cambial derivative cells require a coordination of multiple signals including hormones and peptides. In this mini review, we described the recent discoveries on the regulation of the three developmental processes by several signals such as auxin, cytokinins, brassinosteroids, gibberellins, ethylene, TDIF peptide and their crosstalk in Arabidopsis and Populus. There exists a similar but more complex regulatory network orchestrating vascular cambium development in Populus than that in Arabidopsis. We end up with a look at the future research prospects of vascular cambium in perennial woody plants, including interfascular cambium development and vascular stem cell regulation.